Genetic parameters and investigation of genotype x environment interactions in Nellore x Hereford crossbred for resistance to cattle ticks in different regions of Brazil - Ayres, D. R. [UNESP]; Pereira, R. J. [UNESP]; Boligon, A. A. [UNESP]; Baldi, F. [UNESP]; Roso, V. M.; Albuquerque, L. G. [UNESP] (Springer, 2015)
Data from 6,156 Nellore x Hereford crossbred cattle, distributed in 18 herds located in the Brazilian states of Mato Grosso do Sul (MS), So Paulo (SP), Parana (PR) and Rio Grande do Sul (RS), were analysed in order to investigate genetic variation for resistance to the cattle tick through the estimation of variance components and genetic parameters for counting ticks (Rhipicephalus (Boophilus) microplus) in natural infestation, and also a possible genotype x environment interaction. The tick count data (CC) were transformed to log(10)(CC + 1) and grouped into two regions, defined by cluster analysis and analysed using the method of restricted maximum likelihood. The statistical model included the additive genetic effect as random and fixed effects of the contemporary group (CG) and genetic group (GG) as classificatory and the age of the animal at the time of counting (linear effect) and individual heterozygosity (linear effect, ranging from 0 to 1) as covariates. In the studied regions, the effect of heterosis found was inversely proportional; in other words, the count of ticks decreased with the increase of heterozygosity. The observed heritability estimation for resistance to tick infestation were 0.12 +/- 0.04 and 0.11 +/- 0.04 for groups A (RS and south PR) and B (MS, SP and north PR), respectively. The results of this study suggest that selection for animals resistant to ticks would be possible using the tick count to estimate the genetic value of animals, but with a slow genetic progress. The genetic correlation for tick count between the two groups (A and B) was 0.84 +/- 0.27 and genotype x environment interaction for this trait was not observed in the studied population.
Keywords: Beef cattle; Ectoparasites; REML